ASPECTS OF AGRICULTURAL MARKETING STRATEGIES FOR THE MAIN CROPS SITUATED IN NORTHERN BĂRĂGAN, ROMANIA - Elena LEONTE; Aurel CHIRAN; Cătălin Răzvan VÎNTU; Maria ROBU; Dragoș SMEDESCU; Ștefănița MĂCELARU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In Romania, agriculture is undergoing restructuring and economic development as a result of the changes following the 1989 Revolution. Within this background, agriculture has remained one of the priority branches of the national economy, in close correlation with the level of technical and economic performances achieved worldwide and especially within the agriculture of developed European countries, where technical, scientific and managerial progress has penetrated faster. The authors’ intention is to analyse the main aspects related to the marketing actions for the main crops of grain maize, feed barley and rape, within S.C. AGRAR-M SERV S.R.L. company, based in Bordei-Verde, Lișcoteanca Village, Brăila County, for the reference period 2012-2015. In order to achieve the purpose of this paper, we started from compiling the database for the period under review, and thereafter we presented and analysed the natural conditions in the researched area that influenced the production results and, implicitly, the economic and financial ones.